La agonía judicial en España - Natalia Velilla Antolín (Revista Vasca de Gestión de Personas y Organizaciones Públicas, 2025)
This article analyzes in a global manner the crisis of justice in Spain, which is going through one of its worst moments. Besides the shortage of personnel resources ¿one of the countries in the European Union with the fewest judges per inhabitant, below the European average¿ it has to be added the high rate of litigation, the lack of responsiveness and a nineteenth-century judicial organisation which has not adapted to a changing society. This scenario is fertile ground for distrust in the system, which citizens perceive as highly politicized and subject to serious interference from the other branches of government and the press. The politicisation of justice and the judicialisation of politics do not augur an improvement in the public perception of independence of the Judiciary.